Leading with Flexibility: How Situational Leadership Builds Work Climate and Teacher Professionalism in Early Childhood Education - Khoirun Nisak; Ali Formen; Edi Waluyo (Jurnal Penelitian Pendidikan IPA, 2025)
eacher professionalism is a critical determinant of educational quality, yet it is often influenced by leadership practices and the prevailing work climate in schools. This study addresses the problem of limited empirical evidence regarding how situational leadership contributes to teacher professionalism through the mediating role of work climate in early childhood education. The research aimed to analyze the direct and indirect effects of principals’ situational leadership on teacher professionalism at Raudlatul Athfal Muslimat Nahdlatul Ulama Payaman, Magelang Regency. A quantitative explanatory design was employed involving 88 teachers selected through simple random sampling. Data were collected using validated Likert-scale questionnaires and analyzed through descriptive statistics, path analysis, and the Sobel test to examine mediation effects. The results showed that situational leadership significantly affected work climate (β = 0.62, p < .001) and teacher professionalism (β = 0.35, p < .001). Work climate also had a significant mediating effect (β = 0.25, Sobel z = 3.90, p < .001), explaining 64% of the variance in teacher professionalism (R² = 0.64). The study concludes that adaptive situational leadership strengthens teacher professionalism both directly and indirectly by creating a positive, collaborative, and supportive work climate.